Xishuangbanna Teacher Worship and Perception of Zhang Ha Tradition and Culture - Shengchuan Ruiji (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
This paper uses the phenomenon research methodology to study the teacher worship ceremony and perception of the Zhang Ha tradition culture at Xishuangbanna, which is the Dai culture of the students. Zhang Ha students were representatives and volunteers for informal interviews and conversations; there were 20 people for the study of the perception of Zhang Ha and field data collection in August 2021. The results show that 1) the ceremony represents respect for kindness in the learning of Zhangha and that 2) the organizing of a teacher worship ceremony is not only a tradition but also an activity to strengthen the spirit of students who are studying knowledge that has been accumulated and transmitted from ancient times. 2) Zhang Ha students revealed that the teaching activities of Dai culture inheritance, the motivation of teenagers in this area to learn culture, the cognition and contact channels of culture, and the feedback they received from culture.